Corrigendum to “Associations of Tissue Tumor Mutational Burden and Mutational Status With Clinical Outcomes With Pembrolizumab Plus Chemotherapy Versus Chemotherapy For Metastatic NSCLC [JTO Clinical and Research Reports Vol. 4 No. 1: 100431] - Garassino, Marina C.; Gadgeel, Shirish; Novello, Silvia; Halmos, Balazs; Felip, Enriqueta; Speranza, Giovanna; Hui, Rina; Garon, Edward B.; Horinouchi, Hidehito; Sugawara, Shunichi; Rodriguez-Abreu, Delvys; Reck, Martin; et al. (JTO clinical and research reports, 2025)
[This corrects the article DOI: 10.1016/j.jtocrr.2022.100431.].